Changes in prescribing antithrombotic therapy in patients with atrial fibrillation and myocardial infarction in 2016-2019 - K. G. Pereverzeva; S. S. Yakushin; M. S. Yakushina; A. V. Ezhova; I. A. Bogdanovich; L. A. Simkova (Российский кардиологический журнал)
Aim. To study the changes in prescribing antithrombotic therapy (ATT) among patients with myocardial infarction (MI) and atrial fibrillation (AF), hospitalized in a cardiology hospital in 2016-2017 and 2018-2019.Material and methods. The study included 362 patients with MI and AF in 20162017 — 106 patients, of which 104 were included in the analysis, in 2018-2019 — 256 patients. The median age of patients hospitalized in 2016-2017 was 70,0 (61,0; 78,0) years, in 2018-2019 — 71 (65,0; 79,3) years (p=0,09). There were 60 men (55,6%) in 2016-2017 and 143 (55,8%) in 2018-2019 (p=0,90).Results. In 2016-2017, 80 (76,9%) patients were prescribed dual antiplatelet therapy (DAPT), 17 (16,3%) — therapy with oral anticoagulants (OAC), while 7 (6,7%) of them were as part of triple ATT, 9 (8,7%) — as part of dual ATT (OAC+antiplatelet agent), and 1 (1,0%) — as monotherapy.In 2018-2019, 97 (37, 9%) patients were prescribed DAPT, 140 (54,7%) — OAC therapy, while 115 (44,9%) of them were as part of triple ATT 25 (9,8%) — as a part of dual ATT (OAC+antiplatelet agent). Among all cases of OAC prescription in 2016-2017 and 2018-2019, warfarin was prescribed in 11 (64,7%) and 51 (36,4%) patients,respectively (p=0,02), while rivaroxaban — in 6 (35,3%) and 88 (62,9%) patients, respectively (p=0,03). In 2018-2019, one patient was prescribed dabigatran etexilate.Conclusion. The study revealed that the prescription rate of triple ATT at discharge in 2018-2019 increased 6,7 times compared to 2016-2017 and amounted to 44,9% (n=115) (p<0,001). The prescription rate of OAC in 2018-2019 also increased 3,4 times compared to 2016-2017 and amounted to 54,7% (n=140) (p<0,001).